2017
DOI: 10.14355/sepacs.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Green and Rapid Synthesis of Copper-Doped TiO2 Nanoparticles with Increased Photocatalytic Activity

Abstract: Nano-sized TiO2 photocatalytic water-splitting technology has great potential for low-cost, environmental friendly solarhydrogen production to support the future hydrogen economy. One of the main drawbacks of using TiO2 as a photocatalyst is its band gap of around 3.2 eV for the anatase phase in the near-UV range of the electromagnetic spectrum that uses only small fraction of the solar spectrum. In this study, we have developed an eco-friendly process to synthesize copper doped TiO2 nanoparticles in greener a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The Cu-coated TiO 2 nanoparticle was synthesized following the procedure of [9]. One M CuSO 4 was prepared by dissolving CuSO 4 •5H2O in NH 4 OH (25 wt%).…”
Section: Catalyst Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cu-coated TiO 2 nanoparticle was synthesized following the procedure of [9]. One M CuSO 4 was prepared by dissolving CuSO 4 •5H2O in NH 4 OH (25 wt%).…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…For 1 h at 110 • C, the sediment was dried. The calcination of the as-synthesized Cu-doped TiO 2 was done for 60 min at 500 ± 2 • C [9]. Cu-free TiO 2 was synthesized following the same steps but without using CuSO 4 .…”
Section: Catalyst Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Miller et al [ 18 ] reported that the TiO 2 generates reactive oxygen species when exposed to ultraviolet radiation, nanoparticulate TiO 2 used in antibacterial coatings. Other doped metal and metal oxide particles TiO 2 as silver, gold, copper [ 19 ], ferrous, zinc, cerium, Li/ZnO [ 20 ], MgO/La 2 O 3 , and Mg/Zr/Sr mixed oxide are used for chemical and physical syntheses. Unfortunately, most metal and metal oxides show several drawbacks like the time taking process, uncontrolled temperature, and poor reusability [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…TiO2 is a well-known photocatalyst for removing effluents from wastewater [3][4][5]. The photocatalytic efficiency of TiO2 nanoparticles is improved by doping Cu 2+ metal ions with TiO2 [6]. In this article, we present a simple method to synthesize Cu 2+ -doped TiO2 nanoparticles and investigate the decolourizing effect on degradation of methyl orange (MO) dye under UV light irradiation.…”
Section: Introductionmentioning
confidence: 99%